Borracha natural modificada com ácido hialurônico para aplicações em lesões cutâneas - Miranda, Bruna Vanessa Quevedo (2022)
Skin lesions are considered a public health problem, because in addition to compromising and impairing the quality of life of individuals, they can generate high costs for the health system. In this context, the search for biomaterials that can treat and recover damaged tissues is growing. Studies show that Natural Rubber (NR), extracted from Hevea brasiliensis rubber trees, is a biocompatible biopolymer that has properties that help in the tissue repair process. However, for biomedical applications, it has certain limitations related to the presence of allergenic proteins, hydrophobicity and unsaturated bonds, which limiting its application. In order to overcome these limitations and contribute to the development of new biomaterials, this study aims to deproteinize, epoxidize and graft NR with hyaluronic acid (HA), which is extremely widespread in the medical field due to its bioactive properties. The study also aimed to evaluate the behavior of the new material as a release system for active compounds. For this purpose, the release profile of dry chamomile flower extract (CHAM) was tested due to its therapeutic properties. Therefore, the 1st stage of this work investigated two different methodologies to obtain the proposed material, which were called 1st and 2nd route. Both materials were analyzed by Fourier Transform Infrared Spectroscopy (FTIR), which allowed us to observe signs of deproteinization and esterification grafting between the epoxidized NR and HA molecules. Hydrogen Nuclear Magnetic Resonance Spectroscopy (1H NMR) analysis corroborated the results obtained by FTIR. Thermogravimetry (TG) and Differential Scanning Calorimetry (DSC) thermal analyzes showed that the grafted sample had a lower degradation rate and a higher glass transition temperature (Tg), indicating strong intermolecular interactions. In the 2nd stage, it was found by FTIR that the interaction between the grafted material and CHAM is merely physical. The TG showed that the incorporation of CAM to the modified material is capable of causing a decrease in its thermal stability. The DSC showed that the addition of CHAM can cause a slight increase in the flexibility of the material. Finally, the release profile showed that the grafted material is capable of acting in the CHAM release process, which makes the material promising to be applied in the future in the treatment of skin lesions.